Minimal physical requirements for crystal growth self-poisoning - Whitelam, Stephen; Dahal, Yuba R.; Schmit, Jeremy D. (My University, 2016)
Self-poisoning is a kinetic trap that can impair or prevent crystal growth in a wide variety of physical settings. Here we use dynamic mean-field theory and computer simulation to argue that poisoning is ubiquitous because its emergence requires only the notion that a molecule can bind in two (or more) ways to a crystal; that those ways are not energetically equivalent; and that the associated binding events occur with sufficiently unequal probability. If these conditions are met then the steady-state growth rate is in general a non-monotonic function of the thermodynamic driving force for crystal growth, which is the characteristic of poisoning. Our results also indicate that relatively small changes of system parameters could be used to induce recovery from poisoning. (C) 2016 AIP Publishing LLC.
Citation: Whitelam, S., Dahal, Y. R., & Schmit, J. D. (2016). Minimal physical requirements for crystal growth self-poisoning. Journal of Chemical Physics, 144(6), 7. doi:10.1063/1.4941457
Keywords: Protein Crystallization; Nucleation; Number; Chemistry; Physics